Investigation on the adsorption of phosphorus in all fractions from sediment by modified maifanite. Issue 1 (December 2018) - Liu, Zisen; Zhang, Yi; Han, Fan; Yan, Pan; Liu, Biyun; Zhou, Qiaohong; Min, Fenli; He, Feng; Wu, Zhenbin
Abstract Sediment phosphorus (P) removal is crucial for the control of eutrophication, and thein-situ adsorption is an essential technique. In this study, modified maifanite (MMF) prepared by acidification, alkalization, salinization, calcination and combined modifications, respectively, were first applied to treat sediment P. The morphology and microstructure of MMF samples were characterized by X-ray fluorescence (XRF), Fourier transform infrared (FTIR), X-ray diffraction (XRD), scanning electron microscope (SEM) and Brunauer-Emmett-Teller (BET). Various adsorption parameters were tested, such as dosage of maifanite, time, operation pH and temperature. The adsorption mechanisms were also investigated and discussed. Results showed that CMMF-H2.5-400 (2.5 mol/L H2 SO4 and calcined at 400 °C) exhibited the highest P adsorption capacity. Thus, it was selected as thein-situ adsorbent material to control the internal P loading. Under the optimal conditions of dynamic experiments, the adsorption rates of TP, IP, OP, Fe/Al-P and Ca-P by CMMF-H2.5-400 were 37.22%, 44.41%, 25.54%, 26.09% and 60.34%, respectively. The adsorption mechanisms analysis revealed that the adsorption of P onto CMMF-H2.5-400 mainly by ligand exchange. Results of this work indicated that the modification treatment could improve the adsorption capacity of maifanite, and CMMF-H2.5-400 could be further applied to eutrophication treatment.